PELATIHAN PEMASANGAN PANEL SURYA DAN IOT UNTUK MONITORING LISTRIK BUDIDAYA LELE - Junaidi, Junaidi; Ramadhani, Andrew; Larasati, Mustika Fitri; Abimanyu, Yogi (Smart Education, 2025)
Abstract: The POKDAKAN Tani Makmur group, a freshwater fish farming group in Gerak Tani Village, has problems related to high electricity costs due to dependence on PLN which is used 24 hours a day for operational uses such as aerators, water pumps, lighting, and automatic feeding. To overcome this, this group plans to install a Solar Power Plant (PLTS) and develop an Internet of Things (IoT) application to monitor electricity consumption. PLTS will provide 24-hour electricity from solar energy, expected to reduce operational costs and save electricity costs. The IoT monitoring system will monitor voltage, current, power, energy (kWh), frequency, and power factor, and provide an estimate of electricity costs. This program involves lecturers and students in community service activities, including field surveys, observations, workshop training on PLTS technology and the creation of IoT applications. The goal is to increase harvest yields, provide technological understanding, and broaden the horizons of the POKDAKAN Tani Makmur group in the use of electricity and monitoring electrical loads through IoT. This solution aims to reduce operational costs and increase energy efficiency in catfish farming. Keywords: POKDAKAN prosperous farmers; PLTS; internet of things; pzem sensor; solar charge controller. Abstrak: Kelompok POKDAKAN Tani Makmur, kelompok budidaya ikan air tawar di Desa gerak tani, masalah yang terjadi terkait dengan biaya listrik tinggi karena ketergantungan pada PLN yang digunakan selama 24 jam dalam sehari untuk penggunaaan operasional seperti aerator, pompa air, penerangan, dan pemberian pakan otomatis. Untuk mengatasi hal ini, kelompok ini berencana memasang Pembangkit Listrik Tenaga Surya (PLTS) dan mengembangkan aplikasi Internet of Things (IoT) untuk memantau konsumsi listrik. PLTS akan menyediakan listrik 24 jam dari energi surya, diharapkan dapat mengurangi biaya operasional dan menghemat pengeluaran listrik. Sistem monitoring IoT akan memantau tegangan, arus, daya, energi (kWh), frekuensi, dan faktor daya, serta memberikan estimasi biaya listrik. Program ini melibatkan dosen dan mahasiswa dalam kegiatan pengabdian kepada masyarakat, mencakup survei lapangan, observasi, pelatihan workshop tentang teknologi PLTS dan pembuatan aplikasi IoT. Tujuannya adalah meningkatkan hasil panen, memberikan pemahaman teknologi, dan memperluas wawasan kelompok POKDAKAN Tani Makmur dalam pemanfaatan listrik dan pemantauan beban listrik melalui IoT. Solusi ini bertujuan untuk mengurangi biaya operasional dan meningkatkan efisiensi energi dalam budidaya ikan lele. Kata kunci: internet of things; POKDAKAN tani makmur; PLTS; sensor pzem; solar charge controller.